The Effect of an Audio-Visual Media-Assisted Problem-Based Learning Model and Learning Motivation on the News Writing Skills of Seventh-Grade Students at SMPN 2 Sijunjung - Sevri Ivo; Abdurahman; Nursaid; Tressyalina (Indonesian Journal of Advanced Research, 2026)
The ability to write news texts is one of the essential competencies that junior high school students must master in Indonesian language learning. However, many students still experience difficulties in developing news elements, organizing news structures, and applying appropriate language conventions. This study aimed to examine the effect of Problem-Based Learning (PBL) assisted by audio-visual media and learning motivation on students’ news-writing skills. The research employed a quasi-experimental method using a nonequivalent control group design. The participants were seventh-grade students of SMP Negeri 2 Sijunjung, consisting of an experimental class taught through PBL assisted by audio-visual media and a control class taught using conventional instruction. Data were collected through news-writing performance tests and learning motivation questionnaires. The data were analyzed using independent sample t-tests and two-way ANOVA. The findings revealed that students who learned through PBL assisted by audio-visual media achieved better news-writing skills than those who received conventional instruction. Students with high learning motivation demonstrated higher achievement than students with low motivation. Furthermore, a significant interaction was found between the learning model and learning motivation in influencing students’ news-writing skills. These findings suggest that integrating PBL with audio-visual media can serve as an effective instructional strategy for improving students’ news-writing skills, particularly when supported by strong learning motivation.